(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Citric acid are being used as industrial raw material due to its expanding applications. The growing market and demands there are always need to develop better technique and procedure to enhance the production of yield and also the efficacy of product recovery. The efficacy of different coumarin derivatives was studied on citric acid production with the help of Aspergillus niger NCIM-683.